Fast Switching ITO Free Electrochromic Devices. (4th November 2013) - Jensen, Jacob; Hösel, Markus; Kim, Inyoung; Yu, Jong‐Su; Jo, Jeongdai; Krebs, Frederik C.
<x xml:space="preserve">Abstract</x> Indium‐doped tin oxide free electrochromic devices are prepared by coating electrochromic polymers onto polyethylene terephthalate substrates encompassing two different silver grids as electrodes. One design comprises a flexoprinted highly conductive silver grid electrode, yielding electrochromic devices with a response time of 2 s for an optical contrast of 27%. The other design utilizes an embedded silver grid electrode whereupon response times of 0.5 s for a 30% optical contrast are realized when oxidizing the device. A commercially available conductive poly(3, 4‐ethylenedioxythiophene):poly(4‐styrenesulfonate acid) formulation (PEDOT:PSS) is coated onto the silver grids as a charge balancing polymer, and is in this setting found to be superior to a polypyrrole previously employed in electrochromic devices. In addition, the PEDOT:PSS layer increases the conductivity in the hexagonal grid structure.